SVALex - Volodina, Elena; Pilán, Ildikó; François, Thomas (University of Gothenburg, 2016)
SVALex is a lexicon of receptive vocabulary for Swedish as a second/foreign language (SVA). Like its sister resource, SweLLex, it reports the normalized frequencies of words (lemmas) across six levels of the CEFR (Common European Framework of Reference for Languages). In the same fashion as SweLLex, it contains information on both single word usage, multi-word expressions, as well as information on their usage at different levels, something that is rarely present in the resources of this kind.
The frequencies have been estimated on a corpus of course books, COCTAILL, described in the article:
Elena Volodina, Ildikó Pilán, Stian Rødven Eide and Hannes Heidarsson 2014. You get what you annotate: a pedagogically annotated corpus of coursebooks for Swedish as a Second Language. Proceedings of the third workshop on NLP for computer-assisted language learning. NEALT Proceedings Series 22 / Linköping Electronic Conference Proceedings 107: 128–144.
More details on SVALex resource are provided on this webpage and in article by Volodina et al (2016).

SVALex är en ordlista med receptivt ordförråd för svenska som andraspråk (SVA). Som dess systerresurs, SweLLex, visar listan normaliserade frekvenser for ord (lemmas, dvs grundform + ordklass) på sex nivåer enligt den Gemensamma Europeiska Referensramen för Språk, GERS (eng. CEFR). På samma sätt som i SweLLex, innehåller SVALex information om ord, flerordsenheter, samt deras användning på de olika GERS nivåerna, något som är rätt sällsynt i liknande resurser.
De angivna frekvenserna kommer från en korpus med kursböcker, COCTAILL, se artikel om korpusen här:
Elena Volodina, Ildikó Pilán, Stian Rødven Eide and Hannes Heidarsson 2014. You get what you annotate: a pedagogically annotated corpus of coursebooks for Swedish as a Second Language. Proceedings of the third workshop on NLP for computer-assisted language learning. NEALT Proceedings Series 22 / Linköping Electronic Conference Proceedings 107: 128–144.
Läs mer om SVALex listan på webbsidan och i artikeln skriven av Volodina m.flera (2016).
SVALex
Keywords: Language Technology (Computational Linguistics); word lists; L2; receptive vocabulary; lexicon; Natural Language Processing; Språkbehandling och datorlingvistik